Bi-musical Curricula and “Abyssal Thinking”: The Case of KM Music Conservatory, India - Avis, Rupert (Action, criticism, & theory for music education, 2019)
This article explores student and teacher experiences of bi-musical education at KM Music Conservatory (KM). KM is a higher education institution in Chennai, India, established in 2008 by the internationally renowned film composer, A. R. Rahman. The Conservatory offers various courses, including a Diploma programme validated by Middlesex University, UK, as part of an internationally recognised bachelor's degree in music. Students enrolled in the diploma programme study Western art music and Hindustani classical music as core subjects alongside audio engineering, in what has been described as a bi-musical curriculum. Teacher and student experiences of KM's curriculum indicate bi-musical education can reaffirm colonial, Orientalist, and neoliberal discourses. I argue this should be recognised as an outcome of bi-musical education; however, I also argue that if the generation of these discourses is acknowledged, bi-musical education can bring into dialogue a diverse range of issues that can be used to confront and unsettle colonial ideology, Orientalism, and neoliberalism in engaged ways.